Examining migration factors among generative college graduates: Strategic implications for people attraction, retention, and leadership transfer efforts. Issue 4 (8th August 2022) - Ehrke, Jack; Hastings, Lindsay; Balschweid, Mark; Brodersen, Alex; Burkhart-Kriesel, Cheryl
ABSTRACT: Out-migration of college-educated young adults – a phenomenon that continues to plague rural community vitality – affects not just population size, but also has larger implications for leadership transfer due to impending Baby Boomer retirements. To help community leaders and policy makers simultaneously address forthcoming local leadership transfers as well as young adult attraction and retention efforts, community development scholars and practitioners will benefit from understanding young adults who think and act as "community builders" when choosing their living community after college – the focus of the current descriptive study. Both economic (i.e. available job opportunities) and non-economic (i.e. leadership opportunities) factors were identified as most important to migration decisions with "opportunities to make a difference" and "obtain work-life balance" emerging as highly important community choice factors. These results highlight strategic implications for people attraction, retention, and leadership transfer efforts.